Thymoquinone as a Potential Adjuvant Therapy for Cancer Treatment: Evidence from Preclinical Studies - Mostofa, A.G.M.; Hossain, Md Kamal; Basak, Debasish; Bin Sayeed, Muhammad Shahdaat (Frontiers in Pharmacology, 2017)
Thymoquinone (TQ), the main bioactive component of Nigella sative, has been found to exhibit anticancer effects in numerous preclinical studies. Due to its multitargeting nature, TQ interferes in a wide range of tumorigenic processes and counteract carcinogenesis, malignant growth, invasion, migration, and angiogenesis. Moreover, TQ can specifically sensitize tumor cells towards conventional cancer treatments (e.g. radiotherapy, chemotherapy, immunotherapy) and simultaneously minimize therapy-associated toxic effects in normal cells. In this review, we summarized the adjuvant potential of TQ as observed in various in vitro and in vivo animal models and discussed the pharmacological properties of TQ to rationalize its supplementary role in potentiating the efficacy of standard therapeutic modalities namely surgery, radiotherapy, chemotherapy, and immunotherapy. Altogether, we suggests further comprehensive evaluation of TQ in preclinical and clinical level to delineate its implied utility as a novel complementary adjuvant therapy for cancer treatment.